Participatory design and the learning sciences - Gomez, Kimberley; Kyza, Eleni A.; Mancevice, Nicole (My University, 2018)
Teacher-researcher collaborations are common in design-based research, which is an approach often adopted by learning scientists interested in developing authentic learning environments that are grounded in both theory and practice. In teacher-researcher collaborations participants learn with and from each other. This chapter reports on what we know about teachers and researchers as they co-design innovative environments to promote student learning. The chapter first discusses the foundations, goals and premises of co-design and the forms that teacher-researcher collaborations can take. It then presents the theoretical and methodological commitments of co-design and explores the research themes identified in empirical studies of co-design. The chapter concludes with a discussion of the main challenges participants may face and implications for practice, research and policy.
Keywords: Teachers; Researchers; Co-design